Methods for removing pharmaceuticals from human urine - Mwale, Mwana (Department of Civil Engineering, 2023)
The concept of sustainability is changing the nature of everyday dialogue across many disciplines. The 2030 Sustainable Development Goals provide a practical way to ensure that the basis of sustainability is covered in all disciplines. One of the ways that sustainability can be achieved is through the reuse of various waste streams, such as wastewater. Conventional wastewater treatment plants aim to remove the nutrients in wastewater to prevent problems such as eutrophication. However, this removal process requires a substantial amount of energy. This increases the total cost for the operation of conventional wastewater treatment plants and contributes to greenhouse gas emissions, depending on the source of energy. Nonetheless, some wastewater streams (such as domestic wastewater) have valuable nutrients (nitrogen (N), phosphorus (P) and potassium (K)) which are essential for plant growth). Although urine accounts for 1% of the total volume of domestic wastewater, urine carries most of these key nutrients. For example, urine has 80% N, 70% P and 50% K. Consequently, the source separation and collection of urine provides an opportunity for the recycling of these nutrients for use as fertilizers. Among the many constituents of urine are micropollutants such as pharmaceuticals. Pharmaceuticals pose a challenge for the reuse of urine because fertilizers are required to be free of pharmaceuticals. Therefore, the aim of this work was to find a method for pharmaceutical removal from fresh human urine, while conserving urea. Methodology Four pharmaceutical removal methods were investigated namely: a high pH environment (>12), granular activated carbon, hydrogen peroxide and hydrodynamic cavitation. The pharmaceuticals investigated for this work were grouped into two categories: over the counter (OTC) common pharmaceuticals and the antiretrovirals (ARVs). The OTCs are used to treat a variety of common ailments such as pain, fever, allergies, inflammation, and heart problems in South Africa. The ARVs are used to treat and prevent the human immunodeficiency virus (HIV). Each pharmaceutical removal process had a specific methodology. The methodologies (including the experimental design parameters) were developed based on the literature review of the respective removal methods. Furthermore, the hypothesis for the four removal methods were informed by the results found in literature. The hypotheses were phrased in the following way: the pharmaceuticals can degrade in human urine because the stabilization of human urine using calcium hydroxide increases the pH (˃12), resulting in hydroxide ions that degrade the pharmaceutical molecules while conserving urea; granular activated carbon adsorbs the pharmaceuticals and urea in human urine; the addition of hydrogen peroxide to human urine with a high pH (˃12) forms hydroxyl radicals which degrade the pharmaceutical molecules, along with the excess hydroxide ions from the high pH, while conserving urea; and the hydrodynamic cavitation system generates high energy cavitation bubbles which result in the oxidation of the pharmaceutical molecules while conserving urea. In addition, the conservation of urea during the pharmaceutical removal process for each method was considered. It is known that fresh urine should be stabilized to prevent the enzymatic breakdown of urea into ammonia gas. The stabilization of urine can be achieved by acidification or alkalinization. In this work, urine was stabilized using calcium hydroxide (pH >12.5 at 25°C) and citric acid (pH 2 at 25°C) to keep the urea in solution and thus the investigated pharmaceutical removal methods had to ensure that the degradation of urea did not occur. Hence, the percentage urea degradation for each pharmaceutical removal method was also determined. Pharmaceutical analysis method development Three high performance liquid chromatography (HPLC) methods were used for this work. The first method was for the analysis of over the counter (OTC) common pharmaceuticals, the second for the analysis of antiretrovirals (ARVs) and the third method was for the analysis of a combination of specific OTCs and ARVs. Reverse phase HPLC was used for the three methods and the gradient elution technique was applied for the analysis of the pharmaceuticals. All three methods used acetonitrile as the organic solvent. However, the HPLC method to analyze OTCs and the HPLC method to analyze both the OTCs and the ARVs used a phosphate as an aqueous buffer, while the method to test for the ARVs used a phosphate buffer with the addition of hexanesulfonic acid as an ion pairing reagent. The calibration curves for each pharmaceutical were not developed since the degradation of the pharmaceuticals was expressed as a percentage loss. Nonetheless, the HPLC chromatograms for the individual pharmaceuticals and the mixture of the pharmaceuticals were generated as a reference for the analysis of the pharmaceutical degradation due to the pharmaceutical removal methods. Description and performance of the pharmaceutical removal methods The current work was a comparative study of the pharmaceutical removal methods. All pharmaceutical removal methods were tested in duplicate for the comparative study. Therefore, the standard deviation was not calculated, however, the performance of the pharmaceutical degradation shown in each sample was analyzed in comparison to the other samples. The use of calcium hydroxide as a urine-stabilizing agent was considered as the high pH pharmaceutical removal method. Fresh urine was spiked with pharmaceuticals and then stabilized with calcium hydroxide for at least 75 days. The calcium hydroxide dosage was kept at the recommended calcium hydroxide dosage of 10 g L-1 of fresh urine, to accommodate for urine with different compositions, since urine composition is influenced by factors such as diet. The range of degradation for the over the counter (OTC) common pharmaceuticals due to the high pH was 8 - 44%, with paracetamol and chlorphenamine maleate experiencing the lowest and highest degradation, respectively. Contrary, the range of degradation for the antiretrovirals (ARVs) due to the high pH was 0 - 100%. Abacavir sulfate and nevirapine experienced no degradation, while stavudine, lamivudine, zidovudine and tenofovir experienced complete degradation. The difference in the degradation of the pharmaceuticals was attributed to the difference in the functional groups of the pharmaceuticals. The complete degradation may be attributed to hydrolysis rather than oxidation, including tenofovir which undergoes hydrolysis in basic conditions due to a P – O moiety in its molecular structure. Furthermore, pharmaceuticals with similar functional groups (such as stavudine, lamivudine and zidovudine) showed a similar degradation pattern. In addition, the high pH only resulted in a 4% loss of urea. For the granular activated carbon (GAC) removal method, a GAC column was prepared, through which stabilized urine – spiked with pharmaceuticals – was passed. The adsorption from the GAC removed all the pharmaceuticals by more than 94.7%. However, the GAC also removed 83.4% of the urea present in the stabilized-spiked urine solution. The adsorption of both the pharmaceuticals and the urea was caused by microporous structure of the GAC which provides internal surface area on which the pharmaceutical and urea molecules can attach. Hydrogen peroxide was used as an oxidizing agent to degrade the spiked pharmaceuticals in stabilized urine. The range of degradation for the OTCs, resulting from the addition of hydrogen peroxide to urine with a high pH (˃12), was 0 - 64.7%. Diclofenac and chlorpheniramine maleate did not degrade, while salicylic acid experienced the most degradation (64.7%). On the other hand, the ARVs had a range of degradation of 17.2 - 73.4%. Stavudine experienced the least degradation (17.2%) while lamivudine experienced the most degradation (73.4%). The hydroxyl radicals from the addition of hydrogen peroxide and the excess hydroxide ions from the high pH degraded the pharmaceuticals at varying degrees due to the difference in the functional groups of the pharmaceuticals. Additionally, only 12.6% of the urea was degraded by this pharmaceutical removal method. The hydroxyl radicals generated from the hydrodynamic cavitation (HC) system were used to oxidize the pharmaceutical molecules in the spiked-synthetic urine solution at a low pH (pH 2) and a high pH (pH 12.4). Both the OTCs and the ARVs were analyzed together (due to the high- volume requirement of the experiments) unlike the other degradation methods. The HC system operated at a high pH achieved the highest degradation of 16.6% for chlorphenamine maleate, while paracetamol, zidovudine, lamivudine and stavudine experienced less than 5% degradation. The HC system operated at a low pH reached a degradation range of 10.4 - 49.2%, with paracetamol and zidovudine experiencing the lowest and highest degradation, respectively. The amount of urea which was lost due to the HC system was 6.8%. Thereafter, the HC system was optimized at pH 2, given that the HC system conserved more than 90% of the urea and that it could be readily optimized. The range of degradation improved between 54.5 and 87.6%, with paracetamol and zidovudine again experiencing the highest and lowest degradation, respectively. The difference in the degradation of the pharmaceuticals was attributed to the difference in the oxidation of the functional groups of the pharmaceuticals. Conclusion and applicability The optimized hydrodynamic cavitation (HC) system performed the best out of the four pharmaceutical degradation methods. The optimized HC system had an average pharmaceutical degradation of 74.5%, and resulted in a urea loss of only 5%. The approximate energy required to treat 1 m3 of treated urine using the optimized HC system under the optimized condition was calculated to be 1.84 kWh m-3 . The optimization of the HC system showed potential for the effective removal of pharmaceuticals in urine. Further optimization of the HC system will be beneficial for use as a designated pharmaceutical removal method for the overall urine treatment process.